A Phillips curve for the euro area - Laurence M. Ball; Sandeep Mazumder (European Central Bank (ECB), 2020)
This paper asks whether a textbook Phillips curve can explain the behavior of core inflation in the euro area. A critical feature of the analysis is that we measure core inflation with the weighted median of industry inflation rates, which is less volatile than the common measure of inflation excluding food and energy prices. We find that fluctuations in core inflation since the creation of the euro are well explained by three factors: expected inflation (as measured by surveys of forecasters); the output gap (as measured by the OECD); and the pass-through of movements in headline inflation. Our specification resolves the puzzle of a "missing disinflation" after the Great Recession, and it diminishes the puzzle of a "missing inflation" during the recent economic recovery.
Keywords: E31; E32; 330; Phillips curve; euro area; median inflation; missing inflation; missingdisinflation; core inflation